STUDY OF PERFORMANCE ANALYSIS AND PUBLIC TRANSPORTATION BOK MARTAPURA THESE TABUK RIVER TERMINAL ANTASARI BANJARMASIN - Silfiana Ila Masruroh (Lambung Mangkurat University Press, 2015)
This study is one of the fundamental researches to find out the problems of public transport passengers District region Banjarmasin, South Kalimantan. The purpose of this study was to obtain the performance quality of public transport and to know how many vehicle operating costs. This is done because the public transport is no longer in demand by the public, therefore this study appear to know the reason what causes it to happen.It can be measured in relative terms of service satisfaction criteria ideal public transport among others, are as follows: must be reliable, that is to say all the time available, and takes a short time. There is a comfort in use, meaning the service polite, sheltered from bad weather, easily when dropped or riding a vehicle, available seat at any time, no jostling, has an attractive interior and good seating. A sense of security in driving, which is a sense of security is to avoid accidents and free from crime. And no less important is the travel time and the wait time is not long. Calculation of Operating Costs in the vehicle must be less than the calculation of income, thus profitable for the operator to implement as published in the Public Transport of passengers Guidelines issued by Departemen Public Works.Data in the capture of two types, namely primary data that data is retrieved via public transit, interviews, observation, questioners and secondary data obtained from institutions related to the study, the analysis is done in terms of benefits and costs are measured based constant prices in the beginning, then the results of the analysis of revenues and operating costs of vehicles as a basis to determine the value of the balance of the freight business operations.